2013
DOI: 10.1007/s11999-012-2494-1
|View full text |Cite
|
Sign up to set email alerts
|

Rotator Cuff Integrity Correlates With Clinical and Functional Results at a Minimum 16 Years After Open Repair

Abstract: Level IV, therapeutic study. See Instructions for Authors for a complete description of levels of evidence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
49
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(51 citation statements)
references
References 23 publications
1
49
1
Order By: Relevance
“…Rotator cuff repair is a highly successful procedure in terms of clinical outcomes but rerupture rates remain high 43 44. Several studies have shown that the clinical outcome is significantly poorer if the rotator cuff repair fails 43 45. Tendon healing occurs with sequential inflammatory, proliferative and remodelling phases 46.…”
Section: Discussionmentioning
confidence: 99%
“…Rotator cuff repair is a highly successful procedure in terms of clinical outcomes but rerupture rates remain high 43 44. Several studies have shown that the clinical outcome is significantly poorer if the rotator cuff repair fails 43 45. Tendon healing occurs with sequential inflammatory, proliferative and remodelling phases 46.…”
Section: Discussionmentioning
confidence: 99%
“…8,9 This factor may partially explain the high rate of observed retears at the tendon-bone interface after rotator cuff repair and the subsequent decline in clinical outcomes. [10][11][12][13][14][15] As a result, recent research has focused on the development of biological materials designed to enhance the strength and quality of repaired tissue at the tendon footprint.…”
mentioning
confidence: 99%
“…[46] studied long-term cuff integrity after open rotator cuff repair and tried to determine whether their findings correlated with clinical and functional results. They retrospectively evaluated 67 patients using MR arthrography with a minimum follow-up of 16 years.…”
Section: Clinical Studies Showing Better Results In Patients With Heamentioning
confidence: 99%
“…The results show that this failure does not necessarily lead to poor clinical outcome at least in the short- or mid-term follow up. However, there seems to be a trend towards clinical deterioration in the long-term period after tendon tear recurrence, as was implied from a few clinical studies [46-49]. Also it is obvious that the larger the postoperative defect is, the poorer the clinical outcome ensues.…”
Section: Discussionmentioning
confidence: 99%